2003
DOI: 10.1007/bf02967652
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of mr imaging, galactography and ultrasonography in patients with nipple discharge

Abstract: Among the three modalities, contrast-enhanced three-dimensional MR imaging demonstrated the location and distribution of the lesions most clearly, especially in cases of ductal carcinoma in situ. It has the potential to be a useful diagnostic tool for patients with nipple discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 29 publications
4
45
0
2
Order By: Relevance
“…Rissanen et al (2007) reported that in 52 patients with unilateral nipple discharge, 80% of papillomatous lesions, 58% of other benign lesions, and 20% of malignant lesions were sonographically positive, and among the 6 cases in which duct dilatation was the only sonographic finding, 3 (50%) were malignant lesions and the other 3 (50%) were papillomas and other benign lesions. In a study of 55 patients with bloody ND, Nakahara et al (2003) reported that of all findings, only the hypoechoic masses with smooth margins (NPV = 90.9%) and hypoechoic masses with irregular margins (positive predictive value (PPV) = 85.7%) were statistically significant.…”
Section: Ultrasonography (Us)mentioning
confidence: 97%
See 4 more Smart Citations
“…Rissanen et al (2007) reported that in 52 patients with unilateral nipple discharge, 80% of papillomatous lesions, 58% of other benign lesions, and 20% of malignant lesions were sonographically positive, and among the 6 cases in which duct dilatation was the only sonographic finding, 3 (50%) were malignant lesions and the other 3 (50%) were papillomas and other benign lesions. In a study of 55 patients with bloody ND, Nakahara et al (2003) reported that of all findings, only the hypoechoic masses with smooth margins (NPV = 90.9%) and hypoechoic masses with irregular margins (positive predictive value (PPV) = 85.7%) were statistically significant.…”
Section: Ultrasonography (Us)mentioning
confidence: 97%
“…However, US has limitations with respect to depicting causative lesions of small masses and ductal carcinomas in situ (DCIS), especially those in peripheral regions without ductal dilatation or those in high adipose-containing breasts (Berg & Gilbreath., 2000;Nakahara et al, 2003citing Chung et al, 1995.…”
Section: Ultrasonography (Us)mentioning
confidence: 99%
See 3 more Smart Citations